2021
DOI: 10.7759/cureus.13729
|View full text |Cite
|
Sign up to set email alerts
|

Variable Branching Pattern of Tibial Nerve in the Tarsal Tunnel: A Gross Anatomical Study With Clinical Implications

Abstract: Introduction Tibial nerve is a larger component of the sciatic nerve. It arises from ventral branches (Anterior Division) - L4, L5, S1-S3. Then it travels along the distal border of the popliteus muscle, deep to gastrocnemius and soleus. In the leg, it is accompanied by the posterior tibial vessels and lies in the tarsal tunnel. It divides into the medial calcaneal nerve at the ankle, medial, and lateral plantar nerves under the flexor retinaculum. It carries sensory information. It can adapt to rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 16 publications
(18 reference statements)
1
6
0
Order By: Relevance
“…It originated from the L4-S3 nerve roots composed of motor and sensory fibers; the pelvic floor muscle, bladder sphincters, and bladder detrusor muscle were supplied by the same root [ 36 ]. The tibial nerve is roughly three to four centimeters from the medial malleolus (halfway between the medial malleolus and the Achilles tendon) ( Figure 2 ) [ 37 ].…”
Section: Neuroanatomy Of Posterior Tibial Nervementioning
confidence: 99%
“…It originated from the L4-S3 nerve roots composed of motor and sensory fibers; the pelvic floor muscle, bladder sphincters, and bladder detrusor muscle were supplied by the same root [ 36 ]. The tibial nerve is roughly three to four centimeters from the medial malleolus (halfway between the medial malleolus and the Achilles tendon) ( Figure 2 ) [ 37 ].…”
Section: Neuroanatomy Of Posterior Tibial Nervementioning
confidence: 99%
“…Horwitz [10] first reported the branching pattern of the TN as a classical trifurcation into MPN, LPN, and MCN in the TT. Studies have since explored the variations in the origins of the TN branches in relation to the MM or the malleolarcalcaneal axis (MCA) in order to understand the surgical anatomy of the TTS, [9,[11][12][13][14] which was first described by Kopell and Thompson, [15] and later established by Lam [16] and Keck. [17] Management of TTS often involves surgical nerve decompression and local nerve block.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] This is especially true for the MCN; considerable variations in the number of branches as well as the bifurcation point have been reported. [8][9][10][11][12][13][14] Zhang et al [20] found that MCN can have 1 to 3 branches, whereas Yang et al [18] found up to 5 MCN branches. In the present study, 2 MCN branches were seen to originate at the same point (Type 4), which was also described by Yang et al [18] This variation in the number of MCN branches and its origin could be attributed to racial or individual differences.…”
Section: Discussionmentioning
confidence: 99%
“…It usually emerges as the first branch of the lateral plantar nerve; if not, the normal variant would branch directly from the TN. But in all cases, the origin of Baxter's nerve is distal to that of the MCN 34,35 (►Fig. 22c).…”
Section: Variationsmentioning
confidence: 99%